Battery Ingestion in Children, an Ongoing Challenge: Recent Experience of a Tertiary Center - Lorenzo, Cristina; Azevedo, Sara; Lopes, João; Fernandes, Ana; Loreto, Helena; Mourato, Paula; Lopes, Ana Isabel (Frontiers in Pediatrics, 2022)
Introduction Morbidity related to childhood battery ingestions (BI) has increased recently due to the expanding use of larger lithium cells. A prompt endoscopic removal is vital to prevent severe complications in cases of esophageal batteries (EB). Materials and Methods A retrospective, descriptive study of admissions for BI requiring endoscopic removal in a tertiary hospital's pediatric emergency department (Jan. 2011/Dec. 2020). Results We had 35 cases, with an increasing incidence in the last 6 years; median age, 26 m (8 m-10 years), witnessed ingestion in 86%. On the X-ray: 14 (40%) had an EB, 21 (60%), a gastric battery (GB). Symptoms were present in 57% (100% EB/24% GB), and vomiting was the most frequent (50%). Endoscopy revealed: EB, 13 (37%); GB, 17 (49%); duodenal battery, 1 (3%); no battery, 4 (11%). Median time to removal: EB, 7 h (2 h-21days); GB, 12 h (2 h-3 days). All the patients with EB on the X-ray (14) had severe mucosal injury (Zargar classification): Grade IIIa, 7 (50%); IIIb, 5 (36%); IV, 2 (14%). CT-scan showed perforation in 2 patients (total, 4; 29% of EB). In patients with GB (21), 14 (67%) had mucosal damage; 13 (93%), mild (< Grade III, two esophageal erosions); 1 (7%) IIIa (esophageal ulceration). A statistically significant association between exposure time, younger age or battery size and severity of endoscopic lesions was found in EB location. There were no mortality cases. Acute complications occurred in 57% of EB: infection, 50%; perforation, 29%; pneumomediastinum/stridor, 14%; pneumothorax/subglottic stenosis/hemodynamic instability, 7 vs. 0% GB. Stenosis subsequently developed in 6 (43%) of EB: mild, 4 cases (29%); severe, 2 cases (14%, one resolved after endoscopic dilation; one needed a gastrostomy and esophagocoloplasty). Conclusion We verified recent increase in admissions due to battery ingestions and associated complications, despite the availability of an emergency pediatric endoscopy team. The patients with EB had more severe mucosal injury and poorer short/long-term outcomes. Children with GB had milder lesions, although the presence of a GB did not exclude esophageal injury. The availability of actual data from national referral centers will support advocacy efforts among stakeholders, including industry representatives and policy makers, in preventing worldwide button battery injury.